Second‐order motion‐compensated spin echo diffusion tensor imaging of the human heart. Issue 4 (28th May 2015) - Stoeck, Christian T.; von Deuster, Constantin; Genet, Martin; Atkinson, David; Kozerke, Sebastian
Abstract : Purpose: Myocardial microstructure has been challenging to probe in vivo. Spin echo–based diffusion‐weighted sequences allow for single‐shot acquisitions but are highly sensitive to cardiac motion. In this study, the use of second‐order motion‐compensated diffusion encoding was compared with first‐order motion‐compensated diffusion‐weighted imaging during systolic contraction of the heart. Methods: First‐ and second‐order motion‐compensated diffusion encoding gradients were incorporated into a triggered single‐shot spin echo sequence. The effect of contractile motion on the apparent diffusion coefficients and tensor orientations was investigated in vivo from basal to apical level of the heart. Results: Second‐order motion compensation was found to increase the range of systolic trigger delays from 30%–55% to 15%–77% peak systole at the apex and from 25%–50% to 15%–79% peak systole at the base. Diffusion tensor analysis yielded more physiological transmural distributions when using second‐order motion‐compensated diffusion tensor imaging. Conclusion: Higher‐order motion‐compensated diffusion encoding decreases the sensitivity to cardiac motion, thereby enabling cardiac DTI over a wider range of time points during systolic contraction of the heart.Magn Reson Med 75:1669–1676, 2016. © 2015 Wiley Periodicals, Inc.